Translation of the Convexity Assessment Guide into the Portuguese language - Rafaldini, Bruna Prini; Poletti, Nádia Antônia Aparecida; Ruiz, Paula Buck de Oliveira; Squizatto, Regina Helena; Lopes, Andressa de Oliveira; Oliveira, Niara Carla de (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objectives: Translate the Convexity Assessment Guide into the Portuguese language and perform its semantic, linguistic, conceptual and cultural validation. Methods: Translation study, qualitative descriptive, following the recommended phases: translation, back translation, comparison of original and translated versions back to Portuguese, validation by national experts committee. Results: It was obtained 400 evaluations – 49 annulled and 351 valid – which represents the total used for the agreement analysis of the items. After the analysis, there were six discordant items, reviewed according to the experts’ suggestions, obtaining, then, a greater agreement of 90% in all items evaluated. Conclusion: There was a high level of agreement among the evaluator’s committee, ensuring the continuity of the study with the cross-cultural validation of the Convexity Guide for the Brazilian reality. This research promoted the translation of an instrument that assists in the clinical indication of collector devices for stomas. The validation of the translation into the Portuguese language was obtained, being this the first phase of the process of cross-cultural validation.